Improving Child Survival in Sub-Saharan Africa: Key Environmental and Nutritional Interventions - A. Kofi Amegah (Ubiquity Press, 2020)
Many countries in Sub-Saharan Africa (SSA), did not achieve the Millennium Development Goal 4 target of reducing under-five mortality by two-thirds between 1990 and 2015. A large proportion of under-five deaths in SSA and other developing regions have been attributed to undernutrition and poor household environmental conditions. Failure to address nutritional deficit and household environmental pollution in SSA will therefore likely result in many countries not meeting the Sustainable Development Goal (SDG) 3.2 target which aims to reduce under-five mortality to less than 25 deaths per 1000 livebirths by 2030. This paper pinpoints the nutritional and environmental threats to child health in SSA, and identify interventions that will work best to improve child survival in countries. It is important to broaden the spectrum of interventions for improving child survival beyond health systems strengthening to enable countries meet the SDG 3.2 target. The following interventions are thus proposed: strengthening child welfare clinics through digital technologies; investment in school feeding programmes; addressing household air pollution; and improving water, sanitation and hygiene (WASH) services in basic schools. There are certainly barriers to effective implementation of the proposed interventions in countries but are surmountable with strong political will and involvement of the private sector.